2005
DOI: 10.1021/jm0402061
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of 1-(2-Fluorovinyl)-7-substituted-4-quinolone-3-carboxylic Acid Derivatives, Conformationally Restricted Analogues of Fleroxacin

Abstract: The novel 1-(2-fluorovinyl)-4-quinolone-3-carboxylic acid derivatives Z-15a-c, E-15a-c, Z-16a-c, and E-16a-c, conformationally restricted analogues of fleroxacin (5), were synthesized, and their in vitro antibacterial activity was evaluated. A dehydrosulfenylation of a 2-fluoro-2-[(4-methoxyphenyl)sulfinyl]ethyl group was employed as a key step for the construction of a 2-fluorovinyl group at the N-1 position. It appeared evident that the Z-isomers Z-15a-c and Z-16a-c exhibited 2-to 32-fold more potent in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…The most likely explanation for this difference in the inhibitory concentration between the synthetic caffeic acid and that found in the plant extracts is a slight difference in chemical structure in the naturally extracted compound. Secondary plant products are known to produce different isomers or have slight modifications such as glycosylations, methylations, hydroxylations, or intercalations with metal ions that may lead to differences in function or activity (Len et al, 1996;Kurihara et al, 1997;Vinson et al, 1998;Alam, 2004;Asahina et al, 2005). These slight differences may not be distinguished easily by HPLC analysis alone.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely explanation for this difference in the inhibitory concentration between the synthetic caffeic acid and that found in the plant extracts is a slight difference in chemical structure in the naturally extracted compound. Secondary plant products are known to produce different isomers or have slight modifications such as glycosylations, methylations, hydroxylations, or intercalations with metal ions that may lead to differences in function or activity (Len et al, 1996;Kurihara et al, 1997;Vinson et al, 1998;Alam, 2004;Asahina et al, 2005). These slight differences may not be distinguished easily by HPLC analysis alone.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation showed that the employment of other metal catalysts such as InF 3 , Cu(OTf) 2 , Pd(OAc) 2 , Sc(OTf) 3 and AgNO 3 failed to improve the reaction efficiency (Table 1, entries 4-8). A 63% yield of 3a was obtained when HBF 4 (1.5 equiv) was solely used and an increase of the amount of HBF 4 (2 equiv) or addition of desiccating agents did not obviously improve the reaction (Table 1, entries 9-13). However, the yield was sharply decreased in the presence of bulky bases, indicated that proton acid might be critical to this transformation (Table 1, entries 14-15).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of 4‐quinolones with N‐1 position bearing unsaturated alkyl , amino , sulfonyl , ester , carboxylic acids , imidazole , 1,2,4‐triazole , heterocycles , and N‐1/C‐8 1,2,4‐oxadiazine and N‐1/C‐8 imidazole as well as N‐1 ethylene tethered quinolone dimers were screened for their in vitro antibacterial activities against a panel of clinically relevant Gram‐negative pathogens. In spite of a significant part of them were less potent than the references, the enriched SAR paved the way to the further rational optimization of 4‐quinolones.…”
Section: Structure–activity Relationshipmentioning
confidence: 99%